2014
DOI: 10.1038/ki.2013.253
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining calcineurin inhibition after the diagnosis of post-transplant lymphoproliferative disorder improves renal graft survival

Abstract: Post-transplant lymphoproliferative disorder (PTLD) is an uncontrolled proliferation of transformed lymphocytes fostered by immunosuppression. In addition to chemotherapy, treatment of PTLD includes a reduction of maintenance immunosuppression. Patients with PTLD have an increased risk of graft loss, suggesting that reduced immunosuppression strategy needs to be optimized with regard to graft outcome. Here we retrospectively reviewed 101 cases involving PTLD to identify the risks associated with graft loss. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Lastly, in this series, the precise cause of graft loss was known for only 17% of patients (biopsies were performed in five patients who experienced graft loss; this rate of biopsy is similar to that performed in other studies) . Furthermore, our findings cannot be extended to pediatric patients.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Lastly, in this series, the precise cause of graft loss was known for only 17% of patients (biopsies were performed in five patients who experienced graft loss; this rate of biopsy is similar to that performed in other studies) . Furthermore, our findings cannot be extended to pediatric patients.…”
Section: Discussionsupporting
confidence: 67%
“…Another study showed that rituximab combined with RI (but without chemotherapy) was ineffective in prevention of acute rejection (45% ). Additionally, a recent publication suggested that the maintenance of CNI at a reduced dose appeared to be associated with a lower incidence of de novo anti‐HLA antibodies and better control of the humoral response of the recipient . Despite the risk of rejection, short‐term renal function for patients with PTLD receiving RI, rituximab, and chemotherapy was similar to that of a control population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data remain conflicting, are not conclusive, and have not evaluated an imTOR discontinuing rate after conversion for PTLD. 17,18 Despite the objective data that justify the conversion to imTOR after diagnosis of PLTD, we believe that the suitability of this strategy should be evaluated in an individualized manner, paying attention to each particular case. A constant high level of attention is needed to detect early possible complications related to the use of imTOR, which sometimes may be a diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This results in reduced production of interleukin 2, inhibiting T-cell proliferation. 15,16 According to the Kidney Disease Improving Global Outcomes 2009 clinical practice guidelines, the combination of tacrolimus with an antiproliferative agent, with or without corticosteroids, is the most favored first-line CNI for initial maintenance therapy. Thus, tacrolimusbased regimens are the most commonly used regimens, with 80% of initial immuno suppression and 70% of maintenance immunosup pression received by renal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%